Penggunaan Media Audio pada Anak Tunanetra Tingkat SMP di SLBN 1 Bukittinggi - Lestari, Diyah Ayu; Rozi, Azzuhri; Darimis, Darimis (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Blind people are people who cannot see (totally blind) and can only see light (inattentive). Limitations in seeing can be helped by audio media that emphasizes hearing. This media is suitable because blind children have very sharp hearing when trained continuously. This very sharp hearing can be used for learning by using audio media. The method used in this article is a qualitative method with a qualitative descriptive type with observation and interview data collection techniques, namely research that is intended to describe (describe) a problem. The application of audio teaching materials for blind children in junior high school is the realization of an even education for both normal children and children with special needs. Children with special needs such as the blind can understand learning with audio media that is set using clear and easy-to-understand voices. The advantage of this audio media is that it can easily understand the material because it concentrates on sound which makes feelings and thoughts merge which can cause images and memories that leave an impression. Keywords: Blind, Audio Media, Learning